Modelo Prolab: PractiChamba, una propuesta sostenible para la búsqueda de empleo en el Emporio Comercial de Gamarra - Arias Paredes, Carmen Rosa María (2024)
PractiChamba is an innovative digital solution designed to formalize and optimize the job search and hiring process at the Gamarra emporium in Lima. This project addresses social and economic challenges arising from informality and inefficient and costly hiring processes in Gamarra, which affect both workers and employers. Currently, it is estimated that 70% of jobs in Gamarra are with verbal contracts, generating high job turnover and lack of stability for thousands of workers. Through a mobile application, PractiChamba allows workers to access job offers and training quickly, while employers can optimize the hiring process by reducing costs and search times. The platform contributes to the sustainability and formalization of employment at the emporium, aligning with the Sustainable Development Goals (SDG), especially SDG 8, which seeks to promote decent work and sustainable economic growth. Developed with the Flourishing Business Canvas, PractiChamba shows high potential to reduce unemployment, generate savings in time and resources, and reduce the carbon footprint. In terms of social profitability, it offers tangible benefits such as the reduction of expenses in mobility, paper and time in the search for employment, achieving a Social Net Present Value (Social NPV) of S/. 3,083,906 (USD 811,554). The initial investment for the development and implementation amounts to S/. 382,929, destined for technological infrastructure and development of the application. In addition, the project presents an economic NPV of S/3,906,904 (USD 1,055,920) and an IRR of 131%, evidencing its financial viability. With a five-year perspective, PractiChamba is positioned as a tool to improve employability and quality of life in Gamarra, contributing significantly to the formalization and economic sustainability of one of the largest commercial emporiums in South America.